Phase 2 and biomarker study of trebananib, an angiopoietin‐blocking peptibody, with and without bevacizumab for patients with recurrent glioblastoma. Issue 7 (19th December 2017) - Reardon, David A.; Lassman, Andrew B.; Schiff, David; Yunus, Shakeeb A.; Gerstner, Elizabeth R.; Cloughesy, Timothy F.; Lee, Eudocia Quant; Gaffey, Sarah C.; Barrs, Jennifer; Bruno, Jennifer; Muzikansky, Alona; Duda, Daniel G.; et al.
Abstract : BACKGROUND: Angiopoietins contribute to tumor angiogenesis and may be upregulated as a compensatory factor after vascular endothelial growth factor (VEGF) blockade. The authors performed a phase 2 and biomarker study to evaluate trebananib, an angiopoietin 1 and angiopoietin 2 blocking peptibody, with and without bevacizumab in patients with recurrent glioblastoma. METHODS: Forty‐eight patients who had bevacizumab‐naive, recurrent glioblastoma were treated with trebananib (30 mg/kg weekly) as single agent (n = 11) or combined with bevacizumab (n = 37). The primary endpoint was 6‐month progression‐free survival rate as determined by investigator review. Circulating biomarker levels were assessed before and after study therapy. RESULTS: Trebananib was well tolerated as monotherapy and did not enhance bevacizumab‐associated toxicity. Trebananib had no single‐agent activity, and all treated patients exhibited progressive disease within 2 months. The 6‐month progression‐free survival rate for trebananib plus bevacizumab was 24.3% (95% confidence interval [CI], 12.1%‐38.8%); whereas the median overall survival was 9.5 months (95% CI, 7.5‐4.7 months), and the 12‐month overall survival rate was 37.8% (95% CI, 22.6%‐53.0%). Baseline and post‐treatment changes in circulating vascular VEGF and interleukin‐8 levels were correlated with survival among patients who received trebananib plus bevacizumab. CONCLUSIONS: Angiopoietin 1 and angiopoietin 2 inhibition with trebananib was ineffective as monotherapy and did not enhance the ability of VEGF blockade with bevacizumab to improve the outcomes of patients with recurrent glioblastoma. Cancer 2018;124:1438‐48. © 2017 American Cancer Society . Abstract : Glioblastoma is a highly angiogenic cancer, yet therapeutics that block vascular endothelial growth factor have not improved survival, implicating potential compensatory pathways associated with angiogenesis. In this phase 2 study, angiopoietin inhibition using trebananib with or without bevacizumab is ineffective as treatment for patients with recurrent glioblastoma.